Letters of Friedrich Christian Weber to John Robeson from Russia, 1718-1719 - I. I. Fedyukin; A. D. Novikova (Vestnik MGIMO-Universiteta)
The article examines the correspondence of the Hanoverian resident in Russia Friedrich Christian Weber over the period from January 1718 to the spring of 1720. The set of letters includes over two hundred reports written by the diplomate in French and currently deposited in the French Manuscripts collection of the Bodleian Library of the University of Oxford. The goal of this article is to present this source to the scholarly audience and to offer its preliminary analysis. Although Weber was formally a Hanoverian resident, he represented the interests of England, because the Elector of Hanover, since 1714, was also the monarch of Great Britain. The addressee of Weber’s letters was John Robethon, George I's diplomatic secretary. The article examines various aspects of Weber's diplomatic activities, including the methods he used to collect information in Russia and send it to England, such as bribing Russian officials, resorting to secret agents, ciphers, sending dispatches “under the cover, and others. The letters also reflect the tasks set before him by his government, first of all, investigating the nature of relations between the Russian court and the Jacobites and monitoring the progress of the Congress of Åland, including the views of the Russian and Swedish courts regarding the prospects of a separate peace treaty between them. The article also considers Weber’s approach to the analysis of the international situation and the political situation in Russia. He concluded that a separate treaty between Russia and Sweden was highly unlikely and sought to convey this to his addressee. In spite of this the British government continued to view the ongoing negotiations at Åland as a threat. Beginning in May 1718, the Court of St. James repeatedly instructed Weber to find ways to disrupt Congress. The set of letters shed light on the history of Russian foreign policy at the final stage of the Great Northern War on the eve of the conclusion of the Peace of Nystad.